On translational control by ribosome speed in S. cerevisiae - Kazana, Eleanna; von der Haar, Tobias (Frontiers in RNA Research, 2023)
Introduction: In addition to the widespread and well documented control of protein synthesis by translation initiation, recent evidence suggests that translation elongation can also control protein synthesis rates. One of the proposed mechanisms leading to elongation control is the interference of slow ribosome movement around the start codon with efficient translation initiation. Here we estimate the frequency with which this mode of control occurs in baker’s yeast growing in rich medium. Methods: We interrogate published genome-wide datasets for evidence of transcripts associated with queueing small ribosomal subunits, and confirm results from these surveys using additional experimental work. Results: Our analyses reveal that transcripts from around 20% of yeast genes show evidence of queueing ribosomes, which may be indicative of translation elongation control. Moreover, this subset of transcripts is sensitive to distinct regulatory signals compared to initiation-controlled mRNAs, and such distinct regulation occurs, for example, during the response to osmotic stress. Discussion: Our analyses provide a first quantitative estimate for the prevalence of translational control exerted via the elongation stage in a commonly used model organism, and suggest that transcript under elongation control form a separately addressable RNA regulon.